Nurses’ self-care levels and its related factors: a cross-sectional study - Yunlian Kong; Zirong Tong; Longxiu Liu (BMC Nursing)
Abstract Background Nurses’ self-care has been reported to enhance nurses’ mental health and the quality of care they provide to patients. However, there is a scarcity of studies exploring the factors that influence nurses’ self-care. Consequently, this study aims to investigate the current status of nurses’ self-care ability and its influencing factors, thereby providing a reference for formulating effective strategies to improve nurses’ self-care. Methods This study is a cross-sectional study employing convenience sampling. A general information questionnaire, nurses’ self-care scale, and the flourishing scale were used to explore nurses’ self-care ability and the influencing factors among 1,046 nurses from eight tertiary hospitals in Jiangsu Province, China. Results The total score of nurses’ self-care was (144.63 ± 22.53).The scores for the dimensions of self-care awareness, self-care knowledge, healthy lifestyle, occupational self-acceptance, and inner self-fulfillment were (23.43 ± 4.68), (19.40 ± 4.15), (22.08 ± 4.99), (43.82 ± 5.61), and (35.91 ± 6.00), respectively. The total score of nurses’ flourishing was (45.45 ± 8.83). The self-care scores of nurses with different ages, professional titles, positions, years of working experience, night shift frequency, marital status, number of children, sleep quality, frequency of physical exercise, experience of workplace violence, experience of psychological help-seeking, mental health promotion training experience, relationship with family members, relationship with coworkers, experience of career change, and the flourishing grading level were statistically significantly different(P<0.05). The results of multiple linear regression analysis indicated that the influencing factors of nurses’ self-care competence were sleep quality, relationships with colleagues, and the flourishing grading level(P<0.05). Conclusion It is essential to improve nurses’ self-care ability. Sleep quality, relationship with coworkers, and the flourishing grading level are the factors that influence nurses’ self-care ability. Clinical trial number Not applicable.